Photoelectron‐induced waves: A likely source of 150 km radar echoes and enhanced electron modes - Oppenheim, Meers M. (2016)
VHF radars near the geomagnetic equator receive coherent reflections from plasma density irregularities between 130 and 160 km in altitude during the daytime. Though researchers first discovered these 150 km echoes over 50 years ago and use them to monitor vertical plasma drifts, the underlying mechanism that creates them remains a mystery. This paper uses large‐scale kinetic simulations to show that photoelectrons can drive electron waves, which then enhance ion density irregularities that radars could observe as 150 km echoes. This model explains why 150 km echoes exist only during the day and why they appear at their lowest altitudes near noon. It predicts the spectral structure observed by Chau (2004) and suggests observations that can further evaluate this mechanism. It also shows the types and strength of electron modes that photoelectron‐wave interactions generate in a magnetized plasma.